Effective Integration of Distance Courses Through Project-Based Learning - Malyuga, Elena N.; Petrosyan, Gayane O. (Frontiers in Education, 2022)
The paper aims to single out critical success factors contributing to efficient implementation of distance learning practices and to explain the role of project-based learning in ensuring effective teaching of profession-oriented foreign language in a distance format. The authors argue in favor of distance learning as a beneficial educational tool providing for the training of large groups of people regardless of the place of residence and placing a priority on students’ individual capacities. Study design included a preliminary survey of 150 respondents specializing in the natural sciences and the humanities identifying the key analysis criteria, a complex of experimental online lessons incorporating project-based teaching principles, and a summarizing questionnaire verifying respondents’ post-experiment outlooks. The methodology of empirical research was based on a systematic approach and deployed the methods of pedagogical observation, project-based teaching, sociological research, and statistical analysis using Neural Designer software for calculating questionnaire results. Analyzing the obtained results, the authors conclude that: (1) students specializing in the humanities have a higher motivation to study related minor subjects; (2) interdisciplinary integration using the English language allows to achieve a cumulative effect for major and related minor subjects; (3) interdisciplinary integration based on the project method is an effective means of improving academic performance in major subjects; (4) interdisciplinary integration based on the project method makes it possible to acquaint students with the best practices in their chosen specialty; (5) project method allows to achieve related didactic goals – self-expression, independent continuous learning and the formation of professional competencies.